Musical accompaniment in training as a factor in optimizing the psychophysiological state of young rugby players aged 16-17 years - V.E. Kalinicenko; Zh.L. Kozina; M.Ayaz. Ahmad; S.B. Polishchuk; A.I. Chuprina; A.V. Seryy; O. Y Kolman; G. V. Ivanova; M. D. Kudryavtsev (H.S. Skovoroda Kharkiv National Pedagogical University, 2018)
to reveal the influence of the use of musical accompaniment in training on the psychophysiological functions of rugby players of 16-17 years of age. Material. Twenty rugby players from the sports club "KhTF" (16-17 years) took part in the study, 10 athletes entered the control group, 10 entered the experimental group. The experiment was carried out for two months during the preparatory period at the stage of specialized basic training. The experimental group was trained with musical accompaniment. At the beginning and at the end of the experiment, psychophysiological testing was conducted. The following tests were used: the parameters of a simple and complex reaction in various modes of signal feeding, indicators of efficiency and the nervous system were determined. Intergroup and intra-group differences in the tests were determined. Results. The construction of the training and training process in rugby with the musical accompaniment of the training sessions had a positive effect on the psychophysiological state of the athletes. In representatives of the experimental group in the "Response of choice, the number of errors" test, the result was significantly improved. After the experiment, the control and experimental groups became significantly different. Similar data were obtained in the tests "Response time of choice in the feedback mode" and "Mental stability according to the Schulte test". The obtained data testify to the advisability of using musical accompaniment in the training of young rugby players to optimize the psychophysiological state. Conclusions. The developed method of using musical accompaniment is an effective, accessible and reliable means of improving the psychophysiological state of 16-16-year-old rugby players. The use of musical accompaniment positively affects mental endurance, the reaction rate in various modes of signal delivery, stability and strength of the nervous system.